Investigating the Link between Environmental Performance and Corporate Performance in the UK - Boonchan, Poomkaew (2010)
This study is part of the ongoing ‘ERIPS’ project at the University of Nottingham which focus on examining the impact of environmental performance on environmental performance of firms in the UK manufacturing sector. Both primary data which has been obtained by using a questionnaire survey (firm level data) and secondary data obtained from FAME database have been used in this study. Further, structural equation modeling and regression analyses (i.e., mediated and moderated regression analysis) have been used in this study to examine the possibility of a direct impact of environmental performance on firms’ financial performance and indirect effects on the environmental-financial performance links through innovation, operations efficiency and organizational pressures (i.e., societal pressures, internal stakeholder pressures, and economic pressures). It also examines the possibility of an influence of organizational pressures on corporate environmental performance and sees whether this performance has an impact on financial performance of firms or not. After testing four hypotheses, our analysis indicates that (1) investment in environmental performance has a significant positive or neutral impact on financial performance in the same financial period depending on types of investments, supporting Porter’s win-win hypothesis; (2) innovation mediates the relationship between environmental and financial performance; (3) environmental innovation does not have any effect on the relationship between environmental and financial performance; (4) there is a moderating effect of operations efficiency on the relationship between corporate environmental performance and financial performance; (5) societal pressures, internal stakeholder pressures, and economic pressures (represented organizational pressures) mediate the relationship between corporate environmental performance and financial performance; (6) organizational pressures have a significant positive impact on firms’ environmental performance, however, (7) this environmental performance (influenced by organizational pressures) does not affect financial benefits of firms. The study has implications for both future empirical research and company management. For future research, this study points to the need to examine whether other countries have the same experiences (using the key factors identified by this study). Moreover, it should focus more on using actual and more objective data rather than perceptual and subjective measures in order to avoid a bias of outcomes. In addition, it should focus more on a specific country and/or within-industrial sector in order to be applicable for practitioners to apply the results. For company managements, they should improve their environmental performance by investing in innovation, efficiency of operations as well as responding to economic pressures, stakeholder pressures as these will help them save costs and thus improve their financial performance.